Analysis of Factors Influencing Non-Compliance with Traffic Regulations for Motorcycle Users of Mathematics Students UNP - Helma; Indah Permata (Universitas Negeri Padang, 2023)
The number of violations that occurred in 2019–2022 on types of motorcycle vehicles concluded that motorcycle violations in Padang City experienced fluctuations. The number of violations is quite high for students. Based on this incident, this research aims to find out about the factor analysis model and what factors influence non-compliance with motorcycle traffic regulations. The data used is primary data obtained from giving questionnaires to UNP Mathematics student respondents, and factor analysis is used to analyze the data. According to the study's findings, the factors formed were as follows: factor 1 was wearing a national standard helmet, having a driver's license, having a vehicle registration, the vehicle meeting technical requirements based on the law, the driver meeting the requirements based on regulations, and factor 2 was obeying signal lights, obeying traffic signs, and understanding traffic rules.